2021
DOI: 10.1111/bjh.17709
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hospitalisation for thrombosis in adults with primary immune thrombocytopenia, including disease‐specific treatments: a French nationwide cohort study

Abstract: We aimed to assess the risk factors of venous thrombosis (VT) and arterial thrombosis (AT) in adults with primary immune thrombocytopenia (ITP), particularly in relation to treatments. The population comprised all incident primary ITP adults in France between 2009 and 2017 (FAITH cohort; NCT03429660) built in the national health database. Outcomes were the first hospitalisation for VT and AT. Multivariable Cox regression models included baseline risk factors, time-varying exposure to ITP drugs, splenectomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
3
16
1
Order By: Relevance
“…The results of this study showed that the risk for venous thrombosis during hospitalization was observed in patients with a history of thrombosis, history of cancer, old age, and splenectomy. A higher risk of hospitalization for arterial thrombosis was observed in patients with older age, male sex, a history of cardiovascular disease, and splenectomy [147]. Another epidemiological report showed that smoking, hypertension, male gender, a history of thrombosis, and atrial fibrillation were significantly associated with the occurrence of thrombosis in ITP patients [148].…”
Section: Thrombosis Related With Comorbidities In Itp Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study showed that the risk for venous thrombosis during hospitalization was observed in patients with a history of thrombosis, history of cancer, old age, and splenectomy. A higher risk of hospitalization for arterial thrombosis was observed in patients with older age, male sex, a history of cardiovascular disease, and splenectomy [147]. Another epidemiological report showed that smoking, hypertension, male gender, a history of thrombosis, and atrial fibrillation were significantly associated with the occurrence of thrombosis in ITP patients [148].…”
Section: Thrombosis Related With Comorbidities In Itp Patientsmentioning
confidence: 98%
“…Other risk factors such as diabetes, hypertension, cardiovascular disease, old age, and obesity may contribute to the occurrence of thrombotic events alone or in association with additional risk factors related to ITP treatment or ITP as disease. A French nationwide cohort study published in 2021 [147] that included 10,039 patients assessed the risk factor for venous thrombosis and arterial thrombosis for patients with primary immune thrombocytopenic purpura. The results of this study showed that the risk for venous thrombosis during hospitalization was observed in patients with a history of thrombosis, history of cancer, old age, and splenectomy.…”
Section: Thrombosis Related With Comorbidities In Itp Patientsmentioning
confidence: 99%
“…All listed agents were also associated with an increased risk of arterial thrombosis (AT), except for corticosteroids. Rituximab was not associated with an increased risk of either AT or VT 6 …”
mentioning
confidence: 82%
“…Lafaurie et al seeks to address whether different therapies for ITP may contribute to thrombotic risk. 6 Indeed, this would be an important component of the risk-benefit discussion between clinicians and patients when selecting a treatment strategy. Distinguishing the thrombotic risk of ITP-directed therapies from disease-related factors is not an easy task.…”
mentioning
confidence: 99%
See 1 more Smart Citation